Electrochemical Frequency Modulation for Estimating Exchange Current Density in Solid Oxide Fuel Cells. (26th April 2016) - Das, Debanjan; Hall, Derek M.; Lvov, Serguei N.
Abstract : Electrochemical frequency modulation (EFM) was applied for the first time to solid oxide fuel cells (SOFC) to obtain effective exchange current density and transfer coefficient values. Values obtained from EFM data were compared to values obtained from electrochemical impedance spectroscopy (EIS) and linear sweep voltammetry (LSV). A kinetic model based on Butler-Volmer (B-V) equation was used as the basis for the analysis. It was found that the values obtained via EFM were in good agreement with EIS and Tafel analyses. The obtained values for a cell within a SOFC stack closely ranged from 11 - 16 mA cm -2 for effective exchange current density and 0.88 – 1.3 for transfer coefficient with good repeatability.